The “Cup-Shaped” Technique for Uncontained Osteochondral Lesion of the Talus - Ichiro Yoshimura, M.D., Ph.D. (Arthroscopy Techniques, 2013)
The arthroscopic bone marrow stimulation technique is defined as the first-line procedure for an osteochondral lesion of the talus. The containment of the lesion has been reported as 1 of the prognostic factors for clinical outcomes of arthroscopic bone marrow stimulation. It was surmised that lesions without a stable rim lose the protective border, thereby making stable formation of fibrocartilage less likely. The purpose of the cup-shaped technique is to improve the stability of blood clots after arthroscopic bone marrow stimulation in an uncontained lesion. The geometry of the lesion changes from “uncontained” to “contained like,” which improves the stability of the blood clots.